PENCIPTAAN KARYA SENI INSTALASI DENGAN SUMBER IDE SELF INJURY - rahmadewi, ridha; Purwantoro, Agus (TEXTURE Art and Culture Journal, 2024)
Thisfinalprojectistheresultofexperience,andanassessmentofseveralreferences asaformofinterpretationofsocialphenomenaregardingself-injury,thenprocessed and created in the form of installation art. The creation of these works of art aims to inspire people, especially parents, to pay more attention to parenting and education fortheirchildren.Theauthorusesassemblingtechniquesintheprocessoflovingthe work, by liking or combining various objects to create a new unity. By realizing the ideaofself-defeatingperceptionsfromtheauthor'spointofview,itishopedthatthese works of art can not only be enjoyed by art observers, but can also be a source of inspiration and new understanding to the community about how a habit and the application of wrong student patterns can affect personality. a child in a worse direction.